A case study of the growth effect on different species of rubber intercropping with pineapple / Nurshazleen Jalil - Jalil, Nurshazleen (Faculty of Plantation and Agrotechnology, 2018)
Hevea brasiliensis also known as rubber tree is one of major crop in Malaysia which have economic benefits in the long term. Latex produced is getting from the tapping process of it bark and then milky fluid will come out. It took about 4 to 7 years for the rubber tree to be ready for harvested depends on rubber tree’s condition. During young stage of the rubber, farmers planted the cash crop such as pineapple (Ananas comosus) which help in generating extra income. This is known as intercropping system which is planting two or more cropping at the same planting area on the same time. This case study will focus on species of rubber intercrop with pineapple at Lakai, Negeri Sembilan. The objectives of this case study are to identify growth performance of different variety of rubber and which is the best species of rubber in intercropping with the pineapple. The data of growth performance of rubber were collected from September to November 2017. Hevea pauciflora has the best growth performance among those species of rubber. The results obtained there is significant of different species of rubber intercrop with pineapple in term of number of leaves. The conclusion is intercropping system not only gives extra income to the farmers but it is does not have any adverse competitive effect to the rubber plant.